'Forgotten as first line providers': The experiences of midwives during the COVID-19 pandemic in British Columbia, Canada. (October 2022) - Memmott, Christina; Smith, Julia; Korzuchowski, Alexander; Tan, Heang-Lee; Oveisi, Niki; Hawkins, Kate; Morgan, Rosemary
Abstract: Objective: To explore midwives' experiences working on the frontlines of the COVID-19 pandemic in British Columbia, Canada. Design: Qualitative study involving three semi-structured focus groups and four in-depth interviews with midwives. Setting: The COVID-19 pandemic in British Columbia, Canada from 2020-2021. Participants: 13 midwives working during the first year of the COVID-19 pandemic in British Columbia. Findings: Qualitative analysis surfaced four key themes. First, midwives faced a substantial lack of support during the pandemic. Second, insufficient support was compounded by a lack of recognition. Third, participants felt a strong duty to continue providing high-quality care despite COVID-19 related restrictions and challenges. Lastly, lack of support, increased workloads, and moral distress exacerbated burnout among midwives and raised concerns around the sustainability of their profession. Key conclusions and implications for practice: Lack of effective support for midwives during the initial months of the COVID-19 pandemic exacerbated staffing shortages that existed prior to the pandemic, creating detrimental gaps in essential care for pregnant people, especially with increasing demands for homebirths. Measures to support midwives should combat inequities in the healthcare system, mitigating the risks of disease exposure, burnout, and professional and financial impacts that may have long-lasting implications on the profession. Given the crucial role of midwives in women- and people-centred care and advocacy, protecting midwives and the communities they serve should be prioritized and integrated into pandemic preparedness and response planning to preserve women's health and rights around the world.